Karakterisasi Subgrup Sylow Solvable Dari Grup Poin Senyawa Fosfor Pentaklorida - Ema Carnia Carnia; Sisilia Sylviani; Elah Dewia (Jurnal Sains Dasar, 2017)
Setiap molekul atau senyawa kimia memiliki operasi simetri yang mendeskripsikan keseluruhan karakter dari molekul tersebut. Himpunan dari semua operasi simetri yang berlaku pada suatu senyawa akan membentuk suatu grup. Semua operasi simetri yang berlaku pada senyawa Fosfor pentaklorida membentuk grup poin. Pada paper ini dibahas karakterisasi dari grup poin senyawa Fosfor pentaklorida dilihat dari sudut pandang teori grup. Salah satu hasil yang diperoleh adalah bahwa setiap subgrup Sylow dari senyawa Fosfor pentaklorida merupakan grup solvable.Kata kunci: simetri, grup poin, teori grup, p-subgrup Sylow, solvableCHARACTERIZATION OF SOLVABLE SYLOW SUBGROUP OF POINT GROUP PHOSPHORUS PENTACHLORIDE COMPOUNDPhosphorus pentachloride is a gaseous chemical compound. One of the uses of this compound is a substance that can accelerate the rate of chemical reactions. Phosphorus pentachloride compounds has a molecular geometry shape trigonal bipyramid with a total of 12 symmetry operations. The set of all symmetry operations completed with the operation of the function composition will form a group called the D_3h point group. In this paper discuss the characterization the points group of Phosphorus pentachloride compound from the perspective of group theory. Beginning with point group proofing, then determine all Sylow p-subgroup and normal subgroups of this group.The results obtained were the properties that Sylow 2-subgroup and Sylow 3-subgroup  of Phosphorus pentachloride compounds and slices between Sylow subgroups and normal subgroup is solvable groups. Keywords: Phosphorus pentachloride, point group, group theory, Sylow p-subgroup, solvable